2021
DOI: 10.32758/2782-3040-2021-0-5-34-41
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactants on the wettability of watered viscous oils of some fields in Azerbaijan

Abstract: The results of comparative experimental studies of the effect of various widely used surfactants, as well as sugar refinery waste - after yeast molasses and vinasse on the wettability of the interaction surface during the in-field pipeline transport of oils from fields in the southern region of Azerbaijan and can be successfully used, especially in winter, to regulate fluidity highly emulsion and low solidifying oils. It is shown that the addition of the considered reagents leads to an increase in the contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Three of the mentioned species (H. dispar, H. gallinarum, H. altaicus) belong to the Heterakis genus of the Heterakidae family. Among those species, H. dispar was observed with high intensity and extensiveness in domestic waterfowl in all areas of the country, causing more serious damage to their hosts [9]. Determining the taxonomic position of the species included in the Heterakidae family on the basis of the signs given in the identifiers causes certain difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the mentioned species (H. dispar, H. gallinarum, H. altaicus) belong to the Heterakis genus of the Heterakidae family. Among those species, H. dispar was observed with high intensity and extensiveness in domestic waterfowl in all areas of the country, causing more serious damage to their hosts [9]. Determining the taxonomic position of the species included in the Heterakidae family on the basis of the signs given in the identifiers causes certain difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…and ducks (Anas platyrhynchos dom.) in the country [30][31][32][33][34][35][36][37][38][39]. Among the nematodes, one of the species included in the Heterakidae family is the helminth H. gallinarum.…”
Section: Introductionmentioning
confidence: 99%
“…In other species, the digestive organs were either studied only by histological method or the entire digestive system was not covered (Bogoyavlenskiy et al, 1982;Nasirov et al, 2008). Three species of nematodes (H. gallinarum, H. dispar and H. altaica) belonging to the Heterakidae family were found out of 27 species of helminths recorded in domestic waterfowl in the territory of the Republic of Azerbaijan (Rzayev, 2013;2021a;2021b;2023c;Rzayev et al, 2021a;2021b;Seyibeyli & Rzayev, 2018). We have conducted studies on the ultrastructure of some of the parasites found in birds, fish and other invertebrates in the territory of our country (Nasirov et al, 2020;2024;Seyidbeyli et al, 2020;Rzayev et al, 2020;2022;2023;2024).…”
Section: Introductionmentioning
confidence: 99%